Macroeconomic Analysis of the Poverty Levels on Sumatra Island - Amri Darma Kurniawan S.; Suhendi Suhendi; Andria Zulfa; Lia Nazliana Nasution (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to determine the influence of the Open Unemployment Rate, Gini Ratio and Human Development Index (HDI) on the Poverty Level on Sumatra Island. Research data uses secondary data obtained from the official website of the Central Badan Pusat Statistik (BPS) and Provincial BPS in the form of quantitative data from 10 provinces on the island of Sumatra for the period 2010 - 2023. The research uses the Panel Data Regression Method with the Eviews 12 Student Lite version of the software program. The regression model chosen for this research is the Random Effect Model (REM). The results of data analysis show that the Open Unemployment Rate, Gini Ratio and Human Development Index simultaneously have a significant effect on the Poverty Level on Sumatra Island. Partially, the Open Unemployment Rate has a significant positive effect on the Poverty Rate. Likewise, the Human Development Index has a significant negative effect on Poverty Levels. On the other hand, the Gini Ratio does not have a significant negative effect on the level of poverty on the island of Sumatra during 2010 – 2023.